Developing Junior High School Students English Reading Workbook Based on Local Culture in The Merdeka Curriculum (Development research in the seventh-grade students of SMPN 3 Air Besar in the Academic year 2023-2024): English - Nasri Kurniawan; Dwi Riyanti; Regina (Prodi Tadris Bahasa Inggris, 2024)
This study aimed to develop an English reading workbook based on local culture for students in SMPN 3 Air Besar following the Merdeka Curriculum. The research adopted the Research and Development (R&D) method using the ADDIE model, collecting data through questionnaires, interviews, and direct observations. Analyzed using descriptive statistics and content analysis, the results were used to revise the workbook and improve its effectiveness. The validation phase involved expert judgment from education, English language teaching, and local culture experts, indicating that